Study on water retention characteristics of coastal soils in Northern Zhejiang Province - WANG Hu-bei; LU Sheng-gao (浙江大学学报. 农业与生命科学版, 2001)
The water retention characteristics of coastal soils in Zhejiang Province were studied. Results showed that water retention curves of coastal soils were a typical double-curve and the best modal to characterize the relationship between soil water content and soil suction is logarithmic function. The soil water retention capacity of coastal soils under high suction (80-1 200 kPa) was highly positively correlated with <0.01 mm physical clay content (r=0.961 9**) while soil water retention capacity under low suction (<80 kPa) was mainly controlled by embankment time of coastal soils. The water retention capacity increased with an increase of embankment age of marine deposit. And water specific capacity of coastal soils decreased from 10-1/100 kPa to 10-2-10-3/100 kPa as soil water suction changed from low to high. The content of rapid available water for coastal soils increased with the embankment age of coastal soils.